Characterization of an Enzyme-Catalyzed Crosslinkable Hydrogel as a Wound Dressing in Skin Tissue Engineering: Enzyme-Catalyzed Crosslinkable Hydrogels for Skin Tissue Engineering - Nilforoushzadeh, Mohammad Ali; Amiri, Amir Behtash; Shaghaghi, Behrad; Alimohammadi, Alimohammad; Ahmadi, Rahim; Khodaverdi Darian, Ebrahim; Razzaghi, Mohammadreza; Rezaei Tavirani, Mostafa; Zare, Sona (Journal of Lasers in Medical Sciences, 2021)
Introduction: Wound healing can have a very important impact on the patients’ quality of life. For its treatment, wound dressings have vital and effective uses. Indeed, the use of a proper wound dressing can improve the healing process and duration. Recently, wound dressings with unique properties have been prepared using natural hydrogels. In addition to the general wound characteristics, new generations of wound dressings, such as those lasting longer on the wound, can have specific properties such as transferring allogeneic cells to enhance the healing effect and speed up the healing process. The present study aimed to prepare a gelatin-based hydrogel and to characterize it for therapeutic purposes. Methods: In this experimental-laboratory study, a gelatin hydrogel was made using a microbial transglutaminase (mTG) enzyme. The prepared hydrogel was evaluated in terms of appearance, physical, and chemical properties. To investigate the biological properties of the hydrogel, cells were cultured on it and the toxicity of the hydrogel for the cells was investigated. The location of the cells on the hydrogel was imaged via an electron microscope. The absorption and reflectance characteristics of the hydrogel were recorded by optical spectroscopy. Data were collected and statistical analysis was performed. Results: The results showed that the mTG gelatin hydrogel had a uniform pore size and good physical, chemical, and mechanical properties for use in wound healing. Cell experiments showed evident cell proliferation and high viability. The results also revealed that the cells grew vigorously and adhered tightly to the hydrogel. Conclusion: The preparation of a gelatin hydrogel under GMP conditions can be considered in the healing of diabetic wounds and burns. Doi:10.34172/jlms.2021.77.